Pengaruh Penerapan Green Accounting untuk Mengoptimalkan Pengelolaan Pajak Karbon pada Perusahaan Multinasional di Sektor Manufaktur - Anggun Veby Safitriana; Naula Chantika Putri F; Siti Maisyaroh; Maria Yovita P (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of green accounting in carbon tax management in multinational companies in the manufacturing sector. Green accounting is an accounting approach that includes environmental asppects in finansial reporting, aiming to reduce environmental costs and support corporate sustainability. Using quantitative metodts, this study analyzed data form the sustainability report of five manufacturing companies listed on the IDX in 2022. The result of thr analysis show that carbon tax does not have a significant influence on the implementation of green accounting. This show that the implementation of green accounting os more influenced by other factors besides carbon tax policy. These findings reinforce the importance of exploring additional factors that can support the effective implementation of green accounting.